Insulin growth factors regulate the mitotic cycle in cultured rat sympathetic neuroblasts. - DiCicco-Bloom, E (1988)
While neuronal mitosis is uniquely restricted to early development, the underlying regulation remains to be defined. We have now developed a dissociated, embryonic sympathetic neuron culture system that uses fully defined medium in which cells enter the mitotic cycle. The cultured cells expressed two neuronal traits, tyrosine hydroxylase [L-tyrosine, tetrahydropteridine:oxygen oxidoreductase (3-hydroxylating); EC 1.14.16.2] and the neuron-specific 160-kDa neurofilament subunit protein, but were devoid of glial fibrillary acidic protein, a marker for non-myelin-forming Schwann cells in ganglia. Approximately one-third of the tyrosine hydroxylase-positive cells synthesized DNA in culture, specifically incorporating [3H]thymidine into their nuclei. We used this system to define factors regulating the mitotic cycle in sympathetic neuroblasts. Members of the insulin family of growth factors, including insulin and insulin-like growth factors I and II, regulated DNA synthesis in the presumptive neuroblasts. Insulin more than doubled the proportion of tyrosine hydroxylase-positive cells entering the mitotic cycle, as indicated by autoradiography of [3H]thymidine incorporation into nuclei. Scintillation spectrometry was an even more sensitive index of DNA synthesis, revealing a 4-fold insulin stimulation with an ED50 of 100 ng/ml. Insulin-like growth factor I was 100-fold more potent than insulin, whereas insulin-like growth factor II was less potent, suggesting that insulin growth factor type I receptors mediated the mitogenic responses. In contrast, the trophic protein nerve growth factor exhibited no mitogenic effect, suggesting that the mitogenic action of insulin growth factors is highly specific. Our observations are discussed in the context of the detection of insulin growth factors and receptors in the developing brain.